Pendekatan Pembelajaran Berbasis Masalah dalam Upaya Meningkatkan Kemampuan Literasi Statistis pada Matakuliah Statistika Dasar - Sintha Sih Dewanti (LPPM Press, 2013)
This study describes the statistical literacy skill through lecture with a problem-based learning approachin chemistry students of state Islamic university Sunan Kalijaga. The subjects of study are all studentswho take course in even semester basic statistics of academic year 2012/2013. The result shows that theaverage statistical literacy is good (76.21) and has reached the minimum indicators of the pre-determinedsuccess, as well as to the average ability of solving problem (80.54). Problem-solving abilities include: 1)interpreting the problem, 2) collecting information required in resolving problem; 3) recognizing possiblesolution and assessing several options, and 4) drawing conclusion, while the statistical literacy includes:1) interpreting the conclusion; 2 ) critically evaluating conclusion, and 3) communicating informationand statistical message. The average ability of problem solving in the first cycle is (73.88), second cycle is(80.98), third cycle is (86.22), and fourth cycle is (81.10). The average of statistical literacy ability in thefirst cycle is (65.86), second cycle is (80.44), third cycle is (80.88), and fourth cycle is (77.67).